Proceedings of the 41st ACM Technical Symposium on Computer Science Education 2010
DOI: 10.1145/1734263.1734365
|View full text |Cite
|
Sign up to set email alerts
|

Introductory computing students' conceptions of illegal student-student collaboration

Abstract: Academic integrity and cheating are issues of specific importance in computing courses due to the restricted nature of much of our assigned work. Additionally, use of valued pedagogical and professional practices such as pair programming can muddy the waters when it comes to students' understandings and experiences with collaboration. In this study we report on 112 students at the beginning of a second programming course being asked to describe a scenario of student-to-student collaboration that "crosses the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…Other means of improving culture are studied by Broeckelman-Post in [11], in which it is reported that effective engagement with students, as well as more in-depth discussion of cheating behaviors and expectations, can have a significant effect on deterring cheating. An approach to defining cheating that also uses cultural/attitudinal factors is presented by Stepp and Simon in [12]. The authors asked students to define the act of cheating as it related to their own course assignments.…”
Section: Related Work Backgroundmentioning
confidence: 99%
“…Other means of improving culture are studied by Broeckelman-Post in [11], in which it is reported that effective engagement with students, as well as more in-depth discussion of cheating behaviors and expectations, can have a significant effect on deterring cheating. An approach to defining cheating that also uses cultural/attitudinal factors is presented by Stepp and Simon in [12]. The authors asked students to define the act of cheating as it related to their own course assignments.…”
Section: Related Work Backgroundmentioning
confidence: 99%
“…Similarly, Stepp and Simon found that students frequently cited mitigating circumstances as a reason for unauthorised collaboration [14], and the mitigating circumstances included situations where students had exhausted their own resources to solve the problem.…”
Section: % 19% 69%mentioning
confidence: 98%
“…Regardless of this distinction, it does appear to be considered the most prevalent form of academic misconduct among computing students [5,14], and a number of projects have focused on this aspect of misconduct. Dennis [5] conducted two surveys, one on collusion in programming and another on plagiarism in essays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraser (2014) points out that, owing to the nature of computer science, the best answers will be highly similar, the compiler being 'a relentlessly unforgiving arbiter of correctness' (Roberts, 2002). And it is not just the answers that are confined; Stepp and Simon (2011) have described the constraints on the types of tasks arising in introductory programming assignments.…”
Section: Mathematics -It's Clear Cut Isn't It?mentioning
confidence: 99%